Islamic Moderation in Religious Traditions: A Study of Bid'ah According to Aswaja NU - Ghufron, Muhammad; Syamsuri; Ahmad Fizal Fakhri; Fahruddin Ali Sabri; Umi Chaidaroh (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
This article discusses the concept of bid'ah in the perspective of Ahlus Sunnah wal Jamaah (Aswaja), especially according to Nahdlatul Ulama (NU). This study aims to examine how NU understands bid'ah and how its moderate attitude in responding to various religious traditions that are considered bid'ah. The research method used is a literature review with a qualitative approach. The results of the study show that NU applies the principle of moderation through the concept of maslahah in responding to new traditions that develop in society. Religious traditions such as tawassul, tabarruk, and the commemoration of Maulid are included in the category of bid'ah hasanah, which is accepted because it brings goodness both in social and spiritual aspects. NU's understanding of bid'ah provides a balance between maintaining good old traditions and accepting new innovations that are beneficial to the people.